Perbedaan Tekanan Darah Dan Indeks Massa Tubuh Pada Akseptor Suntik Kombinasi Dan Suntik Depo Medroxyprogesteron Asetat (DMPA) - Rohmi Handayani; Siti Yulaikah (Poltekkes Kemenkes Surakarta, 2017)
Abstract: Blood Pressure, BMI, and Injectable DMPA Injectable Combination. Hormonal contraception is a type of contraception most widely used by women,especially in developed countries because of this effectiveness in preventing pregnancy. Hormonal contraceptives are currently available can be pills, injections or implants. Although effective in preventing pregnancy on the other hand can cause various side effects include is weight gain and increased blood pressure in the acceptor.The purpose of this reasearch is to determine differences in blood pressure rise acceptor combination hormonal injections and blood pressure acceptor DMPA injections and to determine differences in body mass index increase acceptors injectable hormonal combination with a body mass index in injectable DMPA acceptors.Type of this reasearch is an analytic survey with cross sectional study design. The population in this study are all injectable acceptor in the Klaten area totaling 95 512 acceptors. The sample size is 500 samples taken which comprises a group acceptor and acceptor combined injectable DMPA injections. The sampling technique used in this research is purposive sampling. Analysis of data using non-parametric test with Mann Whitney test.There was no significant difference between the increase in systolic blood pressure acceptor and acceptor combined injectable DMPA injections, P = 0.338. There was no significant difference between the increase in diastolic blood pressure acceptor and acceptor combined injectable DMPA injections, P = 0,917.there was significant difference between the increase in BMI acceptor and acceptor combined injectable DMPA injections, P = 0.000.There was no significant difference between the increase in blood pressure and acceptor acceptor combined injectable DMPA injections. There is a significant difference between the increase in BMI acceptor and acceptor combined injectable DMPA injections.